The Effort-Reward Model and Its Effect on Burnout Among Nurses in Ecuador - Alvarado, Luis E.; Bretones, Francisco D.; Rodríguez, Juan A. (Frontiers in Psychology, 2021)
Burnout has harmful consequences for individuals and organizations. The study of its antecedents can help us to manage and prevent it. This research aims to identify the incidence of the Effort-Reward Imbalance model as well as the mediation of the working experience in the burnout processes. For this purpose, we have conducted a study in 629 employees from two hospitals in the city of Guayaquil (Ecuador). For this study, the Spanish version of the Maslach Burnout Inventory was applied, as well as the Effort-Reward Imbalance Questionnaire, along with other socio-demographical and occupational variables. A statistical analysis was performed with the obtained data, using Structural Equation Models (SEM). Results showed that employee effort has a stronger and statistically significant direct effect on emotional burnout, whereas the perception of the obtained reward also had this effect but indirectly in a negative sense, with seniority as a mediating variable.